1977
DOI: 10.1111/j.1744-6570.1977.tb02332.x
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Validity of a Work Sample: A Laboratory Study

Abstract: Concurrent and predictive test validity data and test‐retest reliability data were obtained for a work sample performance measure and two paper and pencil tests in a laboratory setting. The work sample predicted performance on the criterion comparably with the two traditional paper and pencil tests for both concurrent and predictive validity conditions. The results of this study coupled with the inherent advantages of work samples for personnel selection offer a favorable prognosis for future research and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…Also of interest was the finding that previous levels of formal education were related to verbal scores, whereas the hands-on part of the criterion was independent of education and, to some extent, relatively “culture-free” (Smith, 1991). Generally speaking, our results are in line with previous research concerning trainability testing, which suggest that this type of test can have high predictive validity (Robertson & Downs, 1979; Robertson & Kandola, 1989; Aramburu-Zabala, 2001a), and high reliability (Mount, Muchinsky & Hanser, 1977), even if validity tends to attenuate over time (Robertson & Kandola, 1989).…”
Section: Discussionsupporting
confidence: 92%
“…Also of interest was the finding that previous levels of formal education were related to verbal scores, whereas the hands-on part of the criterion was independent of education and, to some extent, relatively “culture-free” (Smith, 1991). Generally speaking, our results are in line with previous research concerning trainability testing, which suggest that this type of test can have high predictive validity (Robertson & Downs, 1979; Robertson & Kandola, 1989; Aramburu-Zabala, 2001a), and high reliability (Mount, Muchinsky & Hanser, 1977), even if validity tends to attenuate over time (Robertson & Kandola, 1989).…”
Section: Discussionsupporting
confidence: 92%
“…Second, studies had to report data from participants who were either actual job applicants or incumbents employed in the job in question. This led us to exclude studies that used a work sample test within a laboratory experiment as either the performance task (e.g., Mount, Muchinsky, & Hanser, 1977; Pritchard, Hollenbeck, & DeLeo, 1980) or as a taped stimulus (e.g., Highhouse & Gallo, 1997). In addition, we excluded studies that focused on training the chronically underemployed or mentally ill (e.g., Franze & Ferrari, 2002), rehabilitating individuals with substance abuse problems such as drug use (e.g., Perone, DeWaard, & Baron, 1979), physical therapy rehabilitation (e.g., Callahan, 1993), and prison inmates (e.g., Grigg, 1948).…”
Section: Methodsmentioning
confidence: 99%
“…A review (101) of selection studies (both published and unpublished) done on nonexempt jobs in the petroleum industry also showed high mean validities for work samples and job knowledge measures. In specifi c studies, Campion (56) fo und much higher concurrent validities for a work sample than fo r paper-and-pencil tests for the job of maintenance mechanic; Gordon & Kleiman (128a) found that the predictive validity fo r a work sample given to police recruits was better than the validity of an ability test; and, in a "lab" study (228), work samples were better than ability tests in refl ecting students' performance levels on the "job" of build ing things with erector set materials.…”
Section: Job Sa Mplesmentioning
confidence: 98%